Interactions between iron and sulfur on the release and dynamics of phosphorus in eutrophic lake sediments - Zhu, Dongdong; Hang, Xiaoshuai; Xu, Minqiang; You, Xiaohui; Wang, Xia; Zhou, Li; Wang, Yan (Journal of soils and sediments, 2025)
Purpose This study aimed to provide in situ evidence for the simultaneous coupling of iron (Fe), sulfide (S(-II)) and phosphorus (P) in the sediment‒water interface (SWI) under anaerobic conditions, thereby enhancing the understanding of the process and mechanism of phosphorus dynamics in eutrophic lake sediments. Materials and methods A 300-day redox-cycle process of aerobic-anoxic-anaerobic was conducted in six periods. High-resolution methods, including diffusive gradient in thin films (DGT) and pore water sampling technology (HR-Peeper) were used to measure Fe, S(-II) and P in the vertical sediment. A 96-well microplate spectrophotometer was employed to detect the dissolved and labile concentrations of Fe(II) and P. The determination of S(-II) was performed using the computer imaging densitometry (CID) scanning method. The ratio of the labile to the soluble concentration ( R diff , C DGT /C SOL ) was calculated to characterize the kinetics of Fe and P release from sediments into the overlying water. Results and discussion The vertical distribution of labile and soluble P, Fe(II) and S(-II) in water and sediment was measured. Findings reveal concentration peaks of these elements at 10–40 mm depth in the SWI, with a significant positive correlation between them. The Fe–P coupling is the main driver of phosphorus release, with S(-II) participating in this process. Organic matter is utilized as an electron donor by sulfate-reducing bacteria, which reduces Fe(III) to Fe(II) and forms FeS precipitation, further promoting the release of Fe–P. The ratio of labile to dissolved concentration (C DGT /C SOL ) peaks (20–40 mm in the SWI) during the transition from aerobic to anaerobic conditions, indicating a strong replenishment ability of sediment to pore water at this stage. Conclusions Under anaerobic conditions, there is a synchronous vertical distribution of P, Fe(II), and S(-II), with the reduction of Fe oxides being the main cause of P release from sediments. Under highly anaerobic conditions, S(-II) indirectly affects the dynamic of P by combining with Fe(II), potentially becoming the dominant factor. Changes in R diff -P and R diff -Fe infer that in the SWI of Lake Taihu sediments, Fe and P have a high capacity to replenish from the sediment particles to the pore water.